Comparative Language Style and Social Criticism in The Poetry Essay Mata Luka Sengkon Karta by Peri Sendi Huizche - Armansyah, Fery; Muarifin, Moch.; Rahmayantis, Marista Dwi (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2025)
This study investigates the use of comparative language styles and social criticism in the poetry essay Mata Luka Sengkon Karta by Peri Sandi Huizche. The analysis identifies seven types of comparative language styles, including simile, metaphor, personification, antithesis, pleonasm, anticipation, and correction. Additionally, it focuses on five categories of social criticism: economic, moral, educational, religious, and political aspects. By applying a qualitative descriptive approach grounded in literary sociology, this research finds that social criticism predominates in the poetry, with 45 instances recorded compared to the seven types of comparative language styles. These poems critically reflect the socio-political conditions and religious practices of their time, highlighting fundamental issues such as injustice, repression, and inequality faced by society. Through various language techniques, Huizche effectively conveys the struggles of marginalized communities, positioning poetry as a powerful medium for social commentary. This study significantly contributes to understanding how literary works can serve as a means of deep social reflection and critique, encouraging readers to contemplate current societal conditions.